Estimasi Cadangan Karbon di Hutan Tanaman Rakyat Desa Batu Jangkih Kabupaten Lombok Tengah - Nahlunnisa, Hafizah; Dinanty, Fawwaz; Yandi, Wahyu Nazri; Susanti, Amelia Dwi; Yuniati Nizar, Wahyu (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2025)
This study aimed to estimate the carbon stock in community plantation forests in Batu Jangkih Village, Central Lombok Regency. Data collection was conducted through field observations using the systematic strip sampling method and analyzed with allometric equations specific to each tree species. The stand consisted of mahogany (Swietenia macrophylla), gmelina (Gmelina arborea), and teak (Tectona grandis), with a total of 6,919 individuals and an average density of 52 trees per hectare. The results showed that gmelina had the largest stand volume (7.05 m³/ha), followed by teak (2.36 m³/ha) and mahogany (1.21 m³/ha). Biomass and carbon stock estimations indicated that gmelina stored the highest amount of carbon (3,565.71 tons/ha), while mahogany and teak stored 1,361.79 tons/ha and 1,302.83 tons/ha, respectively. In total, the community plantation forest stored 81,131.35 tons of carbon or 6,230.33 tons/ha. This study demonstrates that stand volume and carbon storage potential are influenced not only by the number of individuals but also by growth rate and morphological characteristics of each tree species. The community plantation forest in Batu Jangkih Village plays an important role in climate change mitigation while also providing economic benefits to local communities.